Implementation of Arabic Learning Based on Direct Method in Madrasah Kuttab Ibadurrahman - Asih Indartiwi; Romy Mukromah; Zakiyah Arifa (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2020)
Â This study discusses the implementation of learning Arabic by using direct methods in practice. Implementation of learning includes several aspects, including opening lessons, delivering material, and closing lessons. In practice, the direct method of learning Arabic is strongly supported by the regulation of how learning can be realized by the expected results. This relates to learning done to students at the elementary level. In learning a foreign language, elementary students tend to be able to receive language quickly like Mother's tongue, but if taught as a child. The research method used is descriptive qualitative research instruments in the form of observation, interviews, and documentation. Then the data are analyzed by data reduction, data display, and verification. The results of this study are 1) the application of learning Arabic with the direct method is by the needs of students where the teacher is native from Libya. Therefore, Arabic is taught directly by native speakers so students can learn languages according to a fluent dialect, 2) the implementation of learning is said to have fulfilled the rules on aspects of the opening lesson, Â delivering material and closing lesson. However, learning that is carried out by the direct method still teaches in writing skills, whereas in essence, the direct method emphasizes more on listening and speaking skills.Â Penelitian ini membahas implementasi pembelajaran bahasa Arab dengan menggunakan metode langsung dalam praktik. Implementasi pembelajaran mencakup beberapa aspek termasuk membuka pelajaran, menyampaikan materi dan menutup pelajaran. Dalam prakteknya metode pembelajaran langsung bahasa Arab sangat didukung oleh peraturan tentang bagaimana pembelajaran dapat diwujudkan sesuai dengan hasil yang diharapkan. Ini berkaitan dengan pembelajaran yang dilakukan kepada siswa di tingkat dasar. Dalam belajar bahasa asing, siswa sekolah dasar cenderung dapat menerima bahasa dengan cepat seperti bahasa ibu, tetapi jika diajarkan sebagai seorang anak. Metode penelitian yang digunakan adalah instrumen penelitian deskriptif kualitatif dalam bentuk observasi, wawancara dan dokumentasi. Kemudian data dianalisis dengan reduksi data, penyajian data dan kesimpulan. Hasil dari penelitian ini adalah 1) penerapan pembelajaran bahasa Arab dengan metode langsung sesuai dengan kebutuhan siswa di mana guru tersebut berasal dari Libya. Oleh karena itu, bahasa Arab diajarkan langsung oleh penutur asli sehingga siswa dapat belajar bahasa sesuai dengan dialek yang fasih, 2) pelaksanaan pembelajaran dikatakan telah memenuhi aturan tentang aspek membuka pelajaran, menyampaikan materi dan menutup pelajaran. Namun, pembelajaran yang dilakukan dengan metode langsung masih mengajarkan keterampilan menulis, sedangkan pada dasarnya metode langsung lebih menekankan pada mendengarkan dan keterampilan berbicara.